Optimization of Virgin Coconut Oil (VCO) Production Using Papain Enzyme and Tempe Yeast to Enhance Medium Chain Triglycerides (MCT) Content - Enggar Sulistyo Wibisono; Vita Paramita (Vocational College of Universitas Diponegoro, 2025)
Virgin Coconut Oil (VCO) is a high-value derivative product of coconut that contains lauric acid as the major component of Medium-Chain Triglycerides (MCTs). This research aimed to optimize VCO production using a combination of papain enzyme and tempeh yeast to enhance MCT content. The study employed a Central Composite Design-Response Surface Method (CCD-RSM) with two factors: ratio of papain enzyme to tempeh yeast, and fermentation time. The results showed that the yield of VCO ranged from 5.00% to 7.96%, with the highest yield obtained at a fermentation time of 36 h and a papain/yeast ratio of 1/1.33. The water content ranged from 0.90% to 1.25%, free fatty acid (FFA) values ranged between 0.35% and 0.69%, and peroxide values between 1.06–2.41 meq/kg. GC-MS analysis indicated lauric acid (C12:0) as the dominant fatty acid, with a total Medium-Chain Fatty Acid (MCFA) content of 57.77%.